2016
DOI: 10.1177/1558689815585208
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Analysis of Electoral Donations

Abstract: This article reports the results of a nested analysis conducted to evaluate whether or not electoral donations are considered legal bribes. Introduced by Lieberman, nested analysis brings together the strengths of the regression analysis and the case study research by integrating large-N approaches (LNA) with small-N approaches (SNA). The nested analysis uses a sequential sampling model (QUANTITATIVE ! QUALITATIVE) and a nested sampling design (case selection ''on/off the line''). Here, Lieberman's original mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The field of MMR increasingly utilizes the "tremendous potential for making mixed methods relevant to […] visual methodology" (Creswell, 2009, p.101). Especially prevalent is the use of visuals for the presentation of mixed methods designs, which can be done according to established guidelines (Ivankova, Creswell, & Stick, 2006) -see, for instance, Evertsson (2015) and Vrkljan (2009). Faithful to its pragmatic orientation, MMR often applies visuals practically, by studying how visual representations are or can be used to support discourse -see, for instance, Jones (2015) and Quinlan and Quinlan (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The field of MMR increasingly utilizes the "tremendous potential for making mixed methods relevant to […] visual methodology" (Creswell, 2009, p.101). Especially prevalent is the use of visuals for the presentation of mixed methods designs, which can be done according to established guidelines (Ivankova, Creswell, & Stick, 2006) -see, for instance, Evertsson (2015) and Vrkljan (2009). Faithful to its pragmatic orientation, MMR often applies visuals practically, by studying how visual representations are or can be used to support discourse -see, for instance, Jones (2015) and Quinlan and Quinlan (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thaler (2017), from the field of government studies, provides insights from applications of mixed methods research in the examination of political and social violence and conflict, and speaks to the utility and potential hazards of using this methodology at the microscopic and macroscopic levels. Evertsson (2017), from the field of criminology, describes a three-stage process using sequential quantitative sampling (large sample size across 78 countries) to qualitative sampling (small sample size), in an illustration of the application of mixed methods for nested sampling and nested analysis in the study of electoral financing. Shammas (2017), from the field of education, illustrates the use of mixed methods to explore underreporting of discrimination by Arab American and Muslim American community college students, through the use of focus group-generated narratives and survey data.…”
Section: ''In This Issue'' Sectionmentioning
confidence: 99%
“…The point at issue here is that harm to society can be inflicted by actions or inaction (on the complicity continuum) cloaked in legality since states and corporations claim to act within the boundaries of the law. Critical criminologists have illustrated this point in the case of corporate donations to electoral campaigns by calling such donations legal bribes (Friedrichs 2004;Evertsson 2012Evertsson , 2017. Friedrichs (2004: 134) and Evertsson (2012Evertsson ( , 2017 argued that elected politicians deliver undue benefits to their financial supporters (which is illegal) who give them interested money (which is legal), and both parties escape prosecution.…”
Section: State-corporate Crimementioning
confidence: 99%
“…Critical criminologists have illustrated this point in the case of corporate donations to electoral campaigns by calling such donations legal bribes (Friedrichs 2004;Evertsson 2012Evertsson , 2017. Friedrichs (2004: 134) and Evertsson (2012Evertsson ( , 2017 argued that elected politicians deliver undue benefits to their financial supporters (which is illegal) who give them interested money (which is legal), and both parties escape prosecution. Indeed, empirical studies by Peoples and Sutton (2015) and Evertsson (2018) have found that in cases involving electoral financial contributions by corporations, there is observable collusion caused by expected reciprocity originating from a conflicting symbiosis between both parties.…”
Section: State-corporate Crimementioning
confidence: 99%